2005
DOI: 10.1165/rcmb.2004-0372oc
|View full text |Cite|
|
Sign up to set email alerts
|

Gob-5 Is Not Essential for Mucus Overproduction in Preclinical Murine Models of Allergic Asthma

Abstract: Overexpression of Gob-5 has previously been linked to goblet cell metaplasia and mucin overproduction in both in vitro and in vivo model systems. In this study, Gob-5 knockout mice were generated and their phenotype was evaluated in two established preclinical models of allergic asthma. We sought to determine whether the Gob-5-null animals could produce less mucus in response to allergic challenge, and whether this would have any impact on reducing goblet cell metaplasia and airway inflammation. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 28 publications
6
37
0
Order By: Relevance
“…This is at variance with the mCLCA3 protein, which is entirely secreted by intestinal goblet cells (Leverkoehne and Gruber 2002;Gibson et al 2005;Mundhenk et al 2006). This difference and the different cellular locations of mCLCA3 and mCLCA6 argue against a compensatory role of mCLCA6 in the mCLCA3 knockout mouse, which has no apparent spontaneous pathology (Robichaud et al 2005). It remains unknown whether release of the larger Nterminal subunit of mCLCA6 from the membrane as shown here by acid treatment plays any significant role in vivo.…”
Section: Discussionmentioning
confidence: 77%
“…This is at variance with the mCLCA3 protein, which is entirely secreted by intestinal goblet cells (Leverkoehne and Gruber 2002;Gibson et al 2005;Mundhenk et al 2006). This difference and the different cellular locations of mCLCA3 and mCLCA6 argue against a compensatory role of mCLCA6 in the mCLCA3 knockout mouse, which has no apparent spontaneous pathology (Robichaud et al 2005). It remains unknown whether release of the larger Nterminal subunit of mCLCA6 from the membrane as shown here by acid treatment plays any significant role in vivo.…”
Section: Discussionmentioning
confidence: 77%
“…We previously showed that expression of Clca3 (also known as Gob-5) was dramatically increased by IL-13-induced activation of STAT6 in Clara cells (20). It has been reported that Clca3 plays a critical role in mucus production and mucin gene expression in vivo and in vitro (26), although a recent report demonstrates that allergen-and IL-13-induced mucus production and mucin gene induction are unimpaired in Clca3-deficient mice (50). In this study, we report that Clca3 induction was reduced by 71% in mice with Clara cellspecific disruption of Il4ra, indicating that Clca3 induction by allergen is largely dependent on direct effects of IL-4 and/or IL-13 on these cells.…”
Section: Discussionmentioning
confidence: 99%
“…MUC5AC proteins were localized at mucus granules, and hCLCA1 proteins were localized at the circumference of the MUC5AC proteins and goblet cell surface. Although hCLCA1 is overexpressed in the airway epithelium of asthma patients [16], Robichaud et al [33] reported that hCLCA1 is not primarily essential for mucus overproduction. Therefore, mechanisms unrelated to hCLCA1 might also be associated with GCH induced by IL-13.…”
Section: Discussionmentioning
confidence: 99%